2021
DOI: 10.37496/rbz5020200264
|View full text |Cite
|
Sign up to set email alerts
|

Selection indexes for Nellore production system in the Brazilian Pantanal

Abstract: The objective was to develop selection indexes for Nellore cattle raised in full-cycle production system in the Brazilian Pantanal. The resulting offspring are retained as replacements or sold at two years of age. Preliminary analyses explored effects of scale on economic values (EV). However, given the available data, these effects were very small. Presented herein are results from a simulated system consisting of 5,000 cows with all animals maintained on pasture as is typical in Pantanal. The EV were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…Ou seja, compõem aspectos importantes para o aumento da eficiência da cadeia produtiva da pecuária de corte, do nascimento dos animais até o abate. A combinação destas características compondo índice para os diferentes rebanhos poderá ter aspecto importante na condução futura do projeto, inclusive com a inserção dos pesos econômicos das características para estruturar um índice de seleção próprio para os rebanhos, adequados ao sistema e ambiente no qual os rebanhos são manejados (Portes, et al, 2021). Para realizar o aprendizado com os métodos J48, RF e LMT foram utilizado 80% da base de dados para "ensinar" o algoritmo (1357 animais).…”
Section: Resultsunclassified
“…Ou seja, compõem aspectos importantes para o aumento da eficiência da cadeia produtiva da pecuária de corte, do nascimento dos animais até o abate. A combinação destas características compondo índice para os diferentes rebanhos poderá ter aspecto importante na condução futura do projeto, inclusive com a inserção dos pesos econômicos das características para estruturar um índice de seleção próprio para os rebanhos, adequados ao sistema e ambiente no qual os rebanhos são manejados (Portes, et al, 2021). Para realizar o aprendizado com os métodos J48, RF e LMT foram utilizado 80% da base de dados para "ensinar" o algoritmo (1357 animais).…”
Section: Resultsunclassified
“…In the state of Paraná, Brazil, Stoffel & Rambo (2022) found that R$541,112.40 was the investment necessary for an integrated pig finishing farm designed to produce 1,365 animals per production batch. However, in the country, most studies on pig farms focus on the analysis of production costs (Araújo et al, 2016;Portes et al, 2019;Alves et al, 2022) and not on needed investments. In addition to this lack of studies, the reality of pig production in the state of Santa Catarina is quite diverse, which leads to the conclusion that any attempt to estimate a common figure would only be an approximation.…”
Section: Resultsmentioning
confidence: 99%